A Decomposition of Twisted Equivariant -Theory - Gómez, José Manuel; Ramírez, Johana (Symmetry, Integrability and Geometry: Methods and Applications, 2021)
For a finite group, a normalized 2-cocycle α ∈ ²(, ¹) and a -space on which a normal subgroup acts trivially, we show that the α-twisted -equivariant -theory of decomposes as a direct sum of twisted equivariant -theories of parametrized by the orbits of an action of on the set of irreducible α-projective representations of . This generalizes the decomposition obtained in [Gómez J.M., Uribe B., Internat. J. Math. 28 (2017), 1750016, 23 pages, arXiv:1604.01656] for equivariant K-theory. We also explore some examples of this decomposition for the particular case of the dihedral groups ₂ₙ with ≥ 2, an even integer.